2014
DOI: 10.1107/s2053273314086094
|View full text |Cite
|
Sign up to set email alerts
|

Structural insight into the eIF2-eIF2B interaction

Abstract: eIF2B (eukaryotic initiation factor 2B) is a key regulator of translation initiation. It catalyzes guanine nucleotide exchange on eIF2, which delivers the methionylated initiator tRNA to the 40S ribosomal subunit. This exchange reaction is inhibited by the stress-induced phosphorylation of the eIF2 alpha subunit, which leads to global repression of cellular protein synthesis. eIF2B is composed of five subunits. The catalytic gamma/epsilon subcomplex is responsible for nucleotide exchange, while the regulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 0 publications
3
11
0
Order By: Relevance
“…eIF2Bɛ was shown to co-localise with SGs in embryonic mouse cells (Kimball et al, 2003) however more recent studies in yeast suggest eIF2B localises to foci distinct from SGs (Moon and Parker, 2018). In keeping with this, the data presented here demonstrates that mammalian eIF2B bodies are spatially discrete from SGs (Figure 3.6, In its native form eIF2B exists as a heterodecamer (Gordiyenko et al, 2014;Kashiwagi et al, 2016;Kashiwagi et al, 2017;Wortham et al, 2014), however subcomplexes of eIF2B have also been found to exist in mammalian cells, namely eIF2B(βδγε) tetramers and eIF2B(γε) heterodimers (Wortham et al, 2014). The data presented in this study highlight an increased complexity of the localisation of eIF2B within mammalian cells when compared to yeast.…”
Section: Eif2b(α-γ) Subunits Display Unique Localisation Patterns To supporting
confidence: 78%
“…eIF2Bɛ was shown to co-localise with SGs in embryonic mouse cells (Kimball et al, 2003) however more recent studies in yeast suggest eIF2B localises to foci distinct from SGs (Moon and Parker, 2018). In keeping with this, the data presented here demonstrates that mammalian eIF2B bodies are spatially discrete from SGs (Figure 3.6, In its native form eIF2B exists as a heterodecamer (Gordiyenko et al, 2014;Kashiwagi et al, 2016;Kashiwagi et al, 2017;Wortham et al, 2014), however subcomplexes of eIF2B have also been found to exist in mammalian cells, namely eIF2B(βδγε) tetramers and eIF2B(γε) heterodimers (Wortham et al, 2014). The data presented in this study highlight an increased complexity of the localisation of eIF2B within mammalian cells when compared to yeast.…”
Section: Eif2b(α-γ) Subunits Display Unique Localisation Patterns To supporting
confidence: 78%
“…The regulatory and catalytic subunits of eIF2B evolved from ligand regulated protein ancestors. ADP-glucose pyrophosphorylase has a nucleotide bind site that is conserved in its descendant catalytic γ and ε subunits, whereas ribose-1,5bisphosphate isomerase has a phospho-sugar binding pocket conserved in its descendant α, β and δ regulatory subunits (reviewed in Kuhle et al, 2015;Kashiwagi et al, 2017). The ISRIB binding pocket discovered here represents a third conserved feature of eIF2B.…”
Section: Discussionmentioning
confidence: 90%
“…Genetic and structural observations indicate that the inhibitory effect of eIF2(αP) on eIF2B arises from the engagement by the α subunit of eIF2 at a cavity formed by the convergence of the α, β and δ regulatory subunits of the eIF2B decamer (Vazquez de Aldana and Hinnebusch, 1994;Pavitt et al, 1997;Kashiwagi et al, 2016;Bogorad et al, 2017). This regulatory site is distant from the catalytic γε subcomplex of eIF2B and its consecutive Asn-Phe residues that engage the nucleotide binding γ subunit of eIF2 to effect nucleotide exchange (Kashiwagi et al, 2016;Kashiwagi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…who invites authors to provide a succinct discussion of a structure recently published by their laboratory. Amongst other excellent content are gems by Kashiwagi, Ito and Yokoyama on the crustal structure of eIF2B and by Sasaki, Senda and colleagues on a structural reverse genetics approach to understanding PI5P4Kβ activity . http://febs.onlinelibrary.wiley.com/hub/issue/10.1002/(ISSN)1742-4658(CAT)FreeReviewContent(VI)Viewpoints/ are commissioned by Viewpoints Advisory Editors Colin Adrain (Gulbenkian Institute).…”
mentioning
confidence: 99%